A Triple Bottom Line Dominant Logic for Business Sustainability: Framework and Empirical Findings. Issue 2 (2nd April 2016) - Svensson, Göran; Høgevold, Nils; Ferro, Carlos; Varela, Juan Carlos Sosa; Padin, Carmen; Wagner, Beverly
ABSTRACT: Purpose: A limited number of studies have attempted to reveal the mechanism underlying integration amongst the economic, environmental, and social components of business sustainability (BS). BS refers to a company's efforts to go beyond focusing only on profitability, also to manage its environmental, social, and broader economic impact on the marketplace and society as a whole. The research objective of this study is therefore to develop and test a framework of BS, based upon the triple bottom line (TBL) approach. Methodology/approach: Companies with more than 100 employees were identified to take part in the study. Respondents included executives in charge of BS initiatives, such as chief sustainability officers, sustainable business managers, and CEOs. Ultimately, 261 companies agreed to participate. Questionnaires (and an accompanying letter with survey details and contact information on the researchers) were sent to the targeted key informant in the company. A total of 110 usable questionnaires were returned, generating a final response rate of 42.1%. Findings: To assess the underlying pattern of dimensions and items of the BS framework, factor analyses were conducted. An initial factor analysis revealed 3 separate subframeworks of BS (economic, social, and environmental dimensions of the TBL-approach), all of which demonstrate satisfactory factor solutions. A second factor analysis iteration, containing all subframeworks of BS (i.e., 20 dimensions and 60 items) generated a total explained variance of 80%, although the factor loadings of 3 dimensions and their items merged with 3 other dimensions. The final factor solution generated a satisfactory 17-factor solution and explained 83% of the variance, indicating satisfactory convergent, discriminant, and nomological validity, as well as reliability of each dimension. Research implications: The study proposes a BS framework and concludes that the measurement metrics of the BS framework, which were developed and tested, are valid and reliable. Suggestions for applications, research limitations, and further research are provided. The BS framework may be used by companies to assess and monitor their sustainable business practices in the marketplace and society. The framework provides managerial structure and guidance in terms of the dimensions to be taken into consideration and also the items for measuring each of the dimensions of the BS framework in the market and society. The study is not without its limitations and further work is needed to verify the validity and reliability of the empirical findings of the BS framework across contexts and over time. As it stands, the investigation provides a foundation for further research, offering opportunities for updates, amendments, and refinements. Originality/value/contribution: A principal contribution of this study is the empirically developed and tested BS framework. It is based on the elements of the TBL approach, consisting of dimensions and measurement items. The BS framework and its hierarchical layers provide a structured contribution that assesses and monitors the managerial implementation of sustainable business practices and sustainable business models. Furthermore, the structural properties of the BS framework, in relation to contextual variables, provide additional research opportunities for the future.